2013
DOI: 10.1016/j.bbamcr.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone increases αvβ3 integrin expression and affinity through a calcineurin/NFAT pathway

Abstract: The purpose of this study was to determine how dexamethasone (DEX) regulates the expression and activity of αvβ3 integrin. FACS analysis showed that DEX treatment induced expression of an activated αvβ3 integrin. Its expression remained high as long as DEX was present and continued following DEX removal. FACS analysis showed that the upregulation of αvβ3 integrin was the result of an increase in the expression of the β3 integrin subunit. By real time qPCR, DEX treatment induced a 6.2-fold increase (p<0.04) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 46 publications
4
51
0
Order By: Relevance
“…Recent studies examining how DEX regulates the expression of proteins in the TM show that MYOC is not the only protein up regulated as a result of a secondary glucocorticoid response. The β3 integrin subunit in HTM cells is also up regulated by DEX (Faralli et al, 2013) and this study showed that a calcineurin/NFAT (nuclear factor of activated T-cells) pathway may be involved. Calcineurin is a serine/threonine phosphatase that is modulated by intracellular calcium levels.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Recent studies examining how DEX regulates the expression of proteins in the TM show that MYOC is not the only protein up regulated as a result of a secondary glucocorticoid response. The β3 integrin subunit in HTM cells is also up regulated by DEX (Faralli et al, 2013) and this study showed that a calcineurin/NFAT (nuclear factor of activated T-cells) pathway may be involved. Calcineurin is a serine/threonine phosphatase that is modulated by intracellular calcium levels.…”
Section: Introductionmentioning
confidence: 71%
“…This increase was inhibited with cyclosporin A (CsA) (Faralli et al, 2013), an immunosuppressant that forms a complex with cyclophilin leading to an inhibition of calcineurin phosphatase activity (Liu et al, 1991). To determine if CsA could also inhibit the DEX-induced increase in MYOC mRNA, we pre-treated HTM cells with 1 or 10 μM CsA for 1 h prior to the addition of DEX or EtOH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These co-signaling events could be the result of glucocorticoid-induced up-regulation and activation of αvβ3 integrins [67] and ECM proteins [28, 34]. Glucocorticoids have previously been shown to increase production and matrix deposition of unidentified laminins as well as thrombospondin-1, fibronectin and type IV collagen in HTM cells [6870].…”
Section: Discussionmentioning
confidence: 99%